Genetic and Environmental Overlap Between Substance Use and Delinquency in Adolescence: An Analysis by Same-Sex Twins - Boisvert, Danielle L. (Youth violence and juvenile justice, 2019)
During adolescence, many teens begin to experiment with substances and engage in delinquent behavior. The current study seeks to examine whether and to what extent genetic and environmental factors contribute to the association between substance use (i.e., marijuana and alcohol) and different forms of delinquent offending (i.e., violent and nonviolent) across males and females. Analyses were based on same-sex twins (N = 1,072) from the sibling subsample of the National Longitudinal Study of Adolescent to Adult Health (Add Health). The results revealed moderate to large genetic overlap between substance use and delinquent behavior for males. Much of the covariation between alcohol use and offending behavior for females was attributable to common environmental factors, while common genetic factors explained a large portion of the overlap between marijuana use and offending in males and females. The implications of these findings for sex differences in prevention and intervention efforts are discussed from a biosocial perspective.